Comparative analysis of phytochemical properties in preserved and non-preserved butterfly pea flower beverages during storage - Puspitojati Endah; Rahayu Novia Aristi; Fatimah Nur; Sumarna Sumarna (BIO Web of Conferences)
The COVID-19 pandemic has increased public consciousness of the significance of ensuring food safety and promoting good health. The butterfly pea flower (Clitoria ternatea) is recognized for its therapeutic properties, as it harbors valuable components that promote health, notably a rich concentration of antioxidants. This study aims to analyze the changes in phytochemical content in butterfly pea flower beverages with and without preservatives during storage at different temperatures. The method involved preparing butterfly pea flower beverages with the addition of sodium benzoate at concentrations of 0 mg/L, 200 mg/L, 400 mg/L, and 600 mg/L, which were then stored at temperatures of 4°C, 27°C, and 45°C for five weeks. Weekly analyses were performed to quantify the levels of vitamin C, anthocyanins, and free radical inhibition activity. The sensory properties were also conducted to compare hedonic levels between preserved and non-preserved beverages. The findings indicated that the pH of the beverages tended to maintain stability during the storage period. However, there was a notable reduction in the vitamin C concentration. The level of anthocyanin is reduced, particularly when stored at higher temperatures. The inhibition of free radicals showed substantial variance among the different treatments. Sensory properties, including color and aroma, remained generally preferred by the panelists for both preserved and non-preserved beverages. Overall, the addition of sodium benzoate preservatives was effective in maintaining the phytochemical stability and sensory properties of butterfly pea flower beverages during storage.